2011
DOI: 10.1128/aem.01835-10
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid Triggers the “Acid Crash” of Acetone-Butanol-Ethanol Fermentation by Clostridium acetobutylicum

Abstract: Solvent production by Clostridium acetobutylicum collapses when cells are grown in pH-uncontrolled glucose medium, the so-called "acid crash" phenomenon. It is generally accepted that the fast accumulation of acetic acid and butyric acid triggers the acid crash. We found that addition of 1 mM formic acid into corn mash medium could trigger acid crash, suggesting that formic acid might be related to acid crash. When it was grown in pH-uncontrolled glucose medium or glucose-rich medium, C. acetobutylicum DSM 173… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 33 publications
2
67
0
1
Order By: Relevance
“…acetobutylicum, also possess formate dehydrogenases that have been shown to function in the use of formate as a source of one-carbon equivalents. 26 These organisms produce acids during the acidogenic phase of fermentation (acetate and butyrate), and then switch to a solventogenic phase to produce acetone, butanol, and ethanol. The shift from acidogenic to solventogenic phase can be prevented by a phenomenon known as ''acid crash''.…”
Section: Bidirectionally Acting Formate Dehydrogenasesmentioning
confidence: 99%
“…acetobutylicum, also possess formate dehydrogenases that have been shown to function in the use of formate as a source of one-carbon equivalents. 26 These organisms produce acids during the acidogenic phase of fermentation (acetate and butyrate), and then switch to a solventogenic phase to produce acetone, butanol, and ethanol. The shift from acidogenic to solventogenic phase can be prevented by a phenomenon known as ''acid crash''.…”
Section: Bidirectionally Acting Formate Dehydrogenasesmentioning
confidence: 99%
“…The proposed acid crash prevention was careful pH control or metabolism slowdown by lowering cultivation temperature (Maddox et al, 2000). However, very recently the novel possible explanation of this phenomenon has been revealed in intracellular accumulation of formic acid by C.acetobutylicum DSM 1731 (Wang et al, 2011). If acid crash is the phenomenon that usually happens at random in the particular fermentation, so-called strain degeneration is a more serious problem when the production culture loses either transiently or permanently its ability to undergo the metabolic shift and to produce solvents.…”
Section: Challenges Of Butanol Productionmentioning
confidence: 99%
“…the state when the fermentation finished in acidogenic step was sometimes observed from unclear reason, using this strain and milled corn as substrate . Unfortunately, intracellular level of formic acid was not determined and therefore it was not proved or disproved whether acid crash in these cases was also caused by formic acid (Wang et al, 2011). The strain C.beijerinckii CCM 6218 should be identical with the strain C.beijerinckii ATCC 17795 according to data of Czech Collection of Microorganisms.…”
Section: Strains Comparisonmentioning
confidence: 99%
“…They found that at 60˚C ethanol and acetone peaks had exactly the same retention time and, by decreasing the temperature to a sub-ambient temperature of 14˚C, the peaks were separated but some overlap for acetone and butyric acid was still observed. Wang et al [18] used the same column at 15˚C to detect all ABE fermentation broth components and they have found that this column worked only when it was completely clean and needed to be replaced after a few months when the chromatograms showed low resolutions. Finch et al [19] also used the Aminex HPX-87H HPLC column at 30˚C to quantify the components present in ABE fermentation broths.…”
Section: Introductionmentioning
confidence: 99%